Creativity, Resilience and Resistance: Black Birthworkers’ Responses to the COVID-19 Pandemic - Oparah, Julia Chinyere; James, Jennifer E.; Barnett, Destany; Jones, Linda Marie; Melbourne, Daphina; Peprah, Sayida; Walker, Jessica A. (Frontiers in Sociology, 2021)
This article documents the experiences of Black birthworkers supporting pregnant and birthing people and new mamas during the first six months of the COVID-19 pandemic. Building on the methodology and outcomes of Battling Over Birth–a Research Justice project by and for Black women about their experiences of pregnancy and childbirth–the authors utilized a “community-based sheltered-in-place research methodology” to collect the narratives of Black birthworkers, including doulas, certified nurse-midwives (CNMs), homebirth midwives, registered nurses, lactation consultants, community health workers and ob/gyns. The article examines the impact of restrictions put in place by hospitals and clinics, including inadequate or inconsistent care, mandatory testing, separation from newborns, and restrictions on attendance by birth support people, including doulas. Birthworkers shared the innovative approaches that they have devised to continue to offer care and the ways that they have expanded the care they offer to make sure the needs of Black birthing people and new parents are being met during this uncertain time. The article also explores the threats to health, safety, and financial security faced by Black birthworkers as a result of the pandemic, and the overt and subtle forms of racism they had to navigate. Finally, it documents the sources of strength that Black birthworkers have found to sustain them at the frontlines of a maternal health care system in crisis.